Addressing Indonesia’s maritime needs: Jokowi’s ground and sea-level challenges - Noor, Farish A. (2015)
The new Jokowi government faces a major challenge to upgrade its maritime policy to safeguard Indonesia’s economic and defence needs. Besides securing its sea-lanes and overcoming logistical hurdles, the policy has to address the needs of Indonesia’s fishing and sea-based communities across the archipelago.